2022
DOI: 10.1016/j.heliyon.2022.e08886
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven biocomputing pipeline with meta-analysis on high throughput transcriptomics to identify genome-wide miRNA markers associated with type 2 diabetes

Abstract: Discovered a miRNA meta-signature associated with T2D via a data-driven pipeline. Validated in-silico findings against existing evidence and via downstream analyses. Meta-signature could help decode etiologic mechanisms and therapeutic targets of T2D. Broader utility of the pipeline for biomedical evidence synthesis is envisioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Specifically, individual miRNA-disease association studies often suffer from insufficient statistical power due to small sample sizes, are susceptible to many kinds of experimental biases, and may lead to inconsistent results. Very recently, meta-analytic approaches operating on public high-throughput transcriptomic datasets in the NCBI Gene Expression Omnibus (GEO) repository have identified hsa-miR-1260a and hsa-miR-146a-5p as two out of nine potential circulating miRNA markers for incident T2D [61]. The findings we have observed in our study are partially congruent with the small signature of miRNAs that has been derived from the aforementioned meta-analysis [61].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, individual miRNA-disease association studies often suffer from insufficient statistical power due to small sample sizes, are susceptible to many kinds of experimental biases, and may lead to inconsistent results. Very recently, meta-analytic approaches operating on public high-throughput transcriptomic datasets in the NCBI Gene Expression Omnibus (GEO) repository have identified hsa-miR-1260a and hsa-miR-146a-5p as two out of nine potential circulating miRNA markers for incident T2D [61]. The findings we have observed in our study are partially congruent with the small signature of miRNAs that has been derived from the aforementioned meta-analysis [61].…”
Section: Discussionsupporting
confidence: 88%
“…Very recently, meta-analytic approaches operating on public high-throughput transcriptomic datasets in the NCBI Gene Expression Omnibus (GEO) repository have identified hsa-miR-1260a and hsa-miR-146a-5p as two out of nine potential circulating miRNA markers for incident T2D [61]. The findings we have observed in our study are partially congruent with the small signature of miRNAs that has been derived from the aforementioned meta-analysis [61]. However, meta-analytical investigations on circulating miRNAs are unavoidably influenced by the diverse characteristics of available high-throughput miRNA profiling datasets and the unequal quantities of dysregulated miRNAs in T2D patients compared to healthy subjects across different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Genomics strategies are put in place to overcome this limitation by integrating two or more types of genomic data to create a global network of biological interactions [ 6 ]. Data-driven research based on integrative genomics has the potential to unravel disease mechanisms and has become indispensable for the deep understanding of the physiological processes and complex mechanisms underlying disease onset and progression of heterogeneous diseases such as diabetes [ 9 , 12 , 13 ]. Large-scale studies of data compiled from different genomic studies can alleviate the biases of individual studies and unveil possible disease biomarkers and molecular targets amenable to therapeutic intervention [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Integrated genomics studies are still scarce in the context of diabetes [ 14 ], mainly in T1D. Concerning T2D, several studies using individual genomics approaches have been reported; however, these tend to be underpowered due to small sample sizes and lack of consensus on the protocols used, yielding inconsistent findings [ 9 ]. Notwithstanding, further integrative studies are still needed to compile data from complementary omics to add more pieces to the puzzle of the molecular mechanisms underlying diabetes pathogenesis [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation